Sanseviera trifasciata Potential to Reduce Noise Viewed from the Anatomy Structure - Yulianti, L. Indah Murwani (Proceeding International Conference on Global Resource Conservation, 2013)
Sanseviera trifasciata has been known to have great potential in absorbing pollutants. Apparently this plant also has the ability to reduce noise. The purpose of this research is to know the absorption coefficient (Î±) of S. trifasciata leaves and to see anatomic structures. Plants have unique properties because the surfaces of the leaves are covered with fine hairs and the presence of a stoma. The presence of a stoma is quite identical with the state of the surface of the porous panels used to absorb sound. Based on the respondents perception of the existence of plants indoors S. trifasciata showed that most respondents stated the noise level remains the same between the existing Sanseviera plants indoors or not. Meanwhile, based on the results of measurements of the noise level were 7 dB differences in the absence of this plant and after when this plant placed in that area. Absorption coefficients of S. trifasciata leaves were 0.37 in the reference frequency of 500 Hz. To support this assessment study has been done by looking at the anatomical structures and networks existing stomata on leaves to further ensure S. trifasciata owned structure leaves Sanseviera to see similarities with the siding panels to reduce noise.Keywords: absorption coefficients, noise pollution, Sanseviera trifasciataÂ